THE MYTHOLOGY OF KAMPUNG NAGA COMMUNITY - Wahyu Iryana (Al-Albab, 2014)
In order to gain understanding of the meaning of symbolic variants of the myth in Kampung Naga, an objective analysis is required. Therefore, this paper applied the linguistic model study offered by Levi-Strauss as a new step for the objectivity of myth interpretation. The basic assumption of Levi-Strauss’ linguistic model is that myth often display a diverse surface structure, but in fact the diversity is the description of the human deep structure. The selection of this myth was solely based on the life of the Kampung Naga community as part of Sundanese Society. The results indicated that the myth in the religious life of the Kampung Naga community contains a various stories which include the revelation, the reincarnation, and the descent of revelation. These episodes can be constructed into the structure of a Levi-Strauss linguistic model, a binary opposition, namely the mandate giver (active) the mandate recipient (passive). The relationship between the giver and the receiver is vertical (structural) called “structure of three” (regular). From the “structure of three”, the “culinary triangle” can be constructed. From the “combined triangle”, the Batara Guru will also appear to become a central event that other figures have to go through. Finally, it can be stated that the deep structure construction that still refers to the aspect of Javanese cosmology in General.